Análisis y diseño de sistemas de puesta a tierra y sistema integrado de protección contra rayos para subestación de 34,5 kV del Municipio de Guacamayas. (2021)
The objective of this project was to analyze and design the grounding system and the lightning protection system of the 34,5 kilovolt (kV) substation in the municipality of Guacamayas of Empresa de Energía de Boyacá S. A. E. S. P. (EBSA). Therefore, the evaluation of the designs currently installed in the substation was included. For the evaluation, the different elements that make up the integrated lightning protection system and the grounding system were taken as criteria